Pelatihan Pembuatan Pembersih Lantai dari Sereh pada Siswa SMP Islam 02 Pujon - Widyaningrum, Diyah Ayu; Lestari, Enggal (JPM PAMBUDI, 2024)
Various methods and approaches can be used to improve social welfare, namely by empowering. Empowerment can be through training and assistance in making floor cleaners targeting junior high school students. Activities like this can increase students' understanding and skills about the importance of maintaining cleanliness and can create floor cleaning products from the main ingredients of lemongrass and kitchen ingredients that can easily be found in the surrounding environment